Nglebur Laras - Teteh Dayatami (SELONDING, 2018)
The concept of nglebur laras this time is interpreted as the concept of melting the barrel in all situations and conditions in the Karawitan art activity area. The concept can be interpreted as a draw concept, it will not draw if you forget the barrel between them (between the barrel of the pelog and between the barrel of the slendro). Everything always passes between them. Between the barrel of the pelog and the barrel of slendro, half pelog and half slendro it is the behavior of the barrel event which cannot be guessed its existence in the strains of Karawitan's gendhing. Whatever form of sound character is displayed by the barrel of pelog, slendro, and between the two, the fact is that the phenomenon of mixed barrel beating is still called the class of the barrel (of course), and on the concept of karawitan (in particular). The spread of this mixed barrel work is indeed very rapid, especially in the Java area. Pengrawit social society that often makes works by processing mixed tunings is now very spoiled, the habit of looking for the attention of the general public, making the general public become excited by the existence of mixed barrel work, considered uniqueness that is not boring. On the contrary, if the general public understands the condition and essence of the barrel work in general, it will be a suspicion that might be considered damaging the standard and so on.The actualization sought was to create an archipelago music art work with a gender instrument by mixing the duality of the barrel, namely pelog and slendro in one instrument. This Nglebur Laras has multiple interpretations. Nglebur is a term used by gamelan makers / craftsmen, which means the activity of mixing raw materials (iron, tin, copper) into liquid. Nglebur can be interpreted as melting mix or which can also be called mbesot. Nglebur is the main ingredient in making gamelan because iron, tin and copper which are still hard must be cooked first to the point of melting. Then the barrel is the essence that plays an important role in the world of Karawitan. Laras has two special concepts called pelog and slendro. These two different concepts certainly have different characters. Laras is one of the important pieces of furniture. Laras consists of two groups, namely, pelog barrel and slendro barrel. Both types of barrel are one of the two main elements that characterize music. Laras in the world of karawitan has three plural meanings, namely, first; something that is (comfortable) or delicious to be heard or lived, second; namely the sound that has been determined the number of frequencies (penunggul, gulu, dhadha, pelog, lima, nem and item). The third meaning is the scale or scale, which is the arrangement of the notes in the number of sequences and the interval patterns of the tones have been determined. The taste is related to tastes like the expression Rahayu Supanggah in his book Bothekan Karawitan I that 'the barrel is very close to taste, taste can be formed by culture, including local traditions and habits'. The two words that are deliberately combined through all the 'combinations' that the author means are infallibility or an interesting possibility of all possibilities that might occur. It can also be understood that the title of the Nglebur Laras is a synergy or a fusion of all the anxieties in human social culture and social culture of Javanese music (especially the Javanese Gamelan).Keywords: Nglebur, barrel, and unity.